Tikim a taste of Filipino food - Capul, Belina SB.; Fernandez, Doreen; Reyes, Jun. ([Quezon City] Philippine Information Agency)
A brief documentary on the significance of food and the varieties and origins of Philippine cuisine.
Keywords: Cookery -- Philippines; Home economics